Pairwise copula cyclic graphical model for spatial extremes modeling - Zhu, Junting (2014)
Research on extreme events modeling has grown in prominence due to the destructive influence and increasing occurrence rate in recent years. In this work, we focus on spatial extremes, where the extreme values measured at different locations are jointly modeled. The resulting model can, for example, be used to describe the occurrence and measure the risk of catastrophes, such as hurricanes and floods in a spatial domain. Moreover, joint analysis of spatial extremes has the potential to forecast the likelihood of extreme events in one location given that has happened elsewhere.